Заметка об «Адмиралтействе» Осипа Мандельштама (A note on Osip Mandelstam’s “The Admiralty”) - Egeberg, Erik (Poljarnyj vestnik, 2007)
This short article discusses the relationship between Osip Mandelstam's poem "The Admiralty" and Andrej Belyj's novel "The Silver Dove". The author points out that both works contain an unusual metaphor whereby a building is compared to a ship. It is therefore possible that Mandelstam was influenced by Belyj's work, although conclusive evidence cannot be adduced.